2015
DOI: 10.4238/2015.july.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive identification and expression analysis of Hsp90s gene family in Solanum lycopersicum

Abstract: ABSTRACT. Heat shock protein 90 (Hsp90) is a protein produced by plants in response to adverse environmental stresses. In this study, we identified and analyzed Hsp90 gene family members using a bioinformatic method based on genomic data from tomato (Solanum lycopersicum L.). The results illustrated that tomato contains at least 7 Hsp90 genes distributed on 6 chromosomes; protein lengths ranged from 267-794 amino acids. Intron numbers ranged from 2-19 in the genes. The phylogenetic tree revealed that Hsp90 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Except for mutant analysis, two protein inhibitors (geldanamycin (GDA) and radicicol (RAD)) are also widely used to reveal the functions of HSP90s in plants (Baro et al , ; Queitsch et al , ; Samakovli et al , ; Wang et al , ; Watanabe et al , ). So far, the HSP90 gene family has been reported on a genome‐wide basis in several plant species, including Arabidopsis (Krishna & Gloor, ), Populus trichocarpa (Zhang et al , ), tomato (Zai et al , ), chickpea and pigeonpea (Agarwal et al , ), foxtail millet (Singh et al , ), and Brachypodium distachyon (Zhang et al , ). However, cassava HSP90 genes have not been identified and their functions remain to be further characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Except for mutant analysis, two protein inhibitors (geldanamycin (GDA) and radicicol (RAD)) are also widely used to reveal the functions of HSP90s in plants (Baro et al , ; Queitsch et al , ; Samakovli et al , ; Wang et al , ; Watanabe et al , ). So far, the HSP90 gene family has been reported on a genome‐wide basis in several plant species, including Arabidopsis (Krishna & Gloor, ), Populus trichocarpa (Zhang et al , ), tomato (Zai et al , ), chickpea and pigeonpea (Agarwal et al , ), foxtail millet (Singh et al , ), and Brachypodium distachyon (Zhang et al , ). However, cassava HSP90 genes have not been identified and their functions remain to be further characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Although tomato genome has completely sequenced [23]. Most of the published work in tomato is on Hsp90 [24], Hsp70 [25] and small Hsps [26]. Genome wide analysis of Hsp100 family in tomato has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that HSP90s mediate both abiotic and biotic stress resistances in plants [5,[8][9][10], and the expression patterns of HSP90 genes under different biotic and abiotic stress conditions have been widely analysed. HSP90 genes have reported increased expression under heat stress [11] or salt stress [12] in Arabidopsis while being downregulated under cold stress [13] in wheat.…”
Section: Introductionmentioning
confidence: 99%